Evaluation of genetic variation in einkorn wheat originated from west Iran using microsatellite markers - Mohammad Mehdi Poursiahbidi; Kianoosh Cheghamirza; Sohbat Bahraminejad; ahmad arzani; ali ashraf mehrabi (مجله بیوتکنولوژی کشاورزی, 2020)
Objective Genetic diversity in field crops and their wild ancestors plays important role in breeding programs. The aim of this study was to investigate the genetic diversity of einkorn (Triticum monococcum L. ssp. boeoticum) wheat genotypes collected from western parts of Iran using SSR markers.   Material and methods In this study, genetic variation of 163 genotypes from 34 populations of einkorn wheat collected from western parts of Iran was investigated using 19 SSR loci developed in the A genome of hexaploid wheat.   Results In the investigation of 163 einkorn genotypes using 19 microsatellite loci were generated 151 polymorphic alleles with an average of 7.94 per locus. The content of polymorphic information content (PIC) in the studied einkorn genotypes ranged from 0.64 for Xgwm480-3A locus to 0.89 for Xgwm4-4A locus. The mean content of polymorphic information in the studied genotypes was 0.77. According to the results, Xgwm4-4A, Xgwm610-4A and Xgwm282-7A loci were identified as the most suitable primers for studying genetic diversity and differentiation of einkorn wheat genotypes. The mean of Shannon coefficient of 0.16 indicated moderate variation in genotypes under study. The average percentage of polymorphic gene loci in the 34 studied populations was 36.74 and the average heterozygosity was 0.114. Based on analysis of molecular variance for 34 populations, the variations between and within populations were calculated as 7% and 93%, respectively. Cluster analysis based on Jaccard coefficients and UPGMA algorithm classified the einkorn genotypes into 10 distinct groups. The results of the principal coordinate analysis revealed that the two primary vectors explained 29.33% and 24.01% of the total molecular genetic variance, respectively.   Conclusion The results indicated the usefulness of microsatellite markers in identifying and grouping einkorn wheat genotypes, so that the obtained information could be used in breeding projects, germplasm conservation planning and collection of einkorn wheat populations.